Ethical transformation in the Xunzi : a partial explanation - Sung, Winnie (2021)
In this paper, the author attempts to provide a partial explanation of why Xunzi 荀子 thinks that human beings can be transformed in spite of our problematic nature. She argues that Xunzi has implicitly assumed that the reason human feelings can be ordered is that human beings have the capacity for self-reflection. On the proposed account, the process of ethical transformation is one in which the heart/mind reflects upon the characteristically human feelings one has and in doing so, brings others into regard. The proposed interpretation seeks to make sense of Xunzi‟s view on ethical transformation without compromising his claim that human nature is bad. If this is successful, it will also shed light on Xunzi‟s picture of human psychology.